Pharmaceutical aerosols for the treatment and prevention of Tuberculosis - Hanif, Shumaila N M.; Garcia-Contreras, Lucila (Frontiers in Cellular and Infection Microbiology, 2012)
Historically, pharmaceutical aerosols have been employed for the treatment of obstructive airway diseases, such as asthma and chronic obstructive pulmonary disease, but in the past decades their use has been expanded to treat lung infections associated with cystic fibrosis and other respiratory diseases. Tuberculosis (TB) is acquired after inhalation of aerosol droplets containing the bacilli from the cough of infected individuals. Even though TB affects other organs, the lungs are the primary site of infection, which makes the pulmonary route an ideal alternative route to administer vaccines or drug treatments. Optimization of formulations and delivery systems for anti-TB vaccines and drugs, as well as the proper selection of the animal model to evaluate those is of paramount importance if novel vaccines or drug treatments are to be successful. Pharmaceutical aerosols for patient use are generated from metered dose inhalers, nebulizers and dry powder inhalers. In addition to the advantages of providing more efficient delivery of the drug, low cost and portability, pharmaceutical dry powder aerosols are more stable than inhalable liquid dosage forms and do not require refrigeration. Methods to manufacture dry powders in respirable sizes include micronization, spray drying and other proprietary technologies. Inhalable dry powders are characterized in terms of their drug content, particle size and dispersibility to ensure deposition in the appropriate lung region and effective aerosolization from the device. These methods will be illustrated as they were applied for the manufacture and characterization of powders containing anti-tubercular agents and vaccines for pulmonary administration. The influence of formulation, selection of animal model, method of aerosol generation and administration on the efficacy demonstrated in a given study will be illustrated by the evaluation of pharmaceutical aerosols of anti-TB drugs and vaccines in guinea pigs by our group.